171 PREFERRED DRUG PRESCRIBING IN ARKANSAS MEDICAID: THE USE OF LESS SEDATING ANTIHISTAMINES FOR THE TREATMENT OF SEASONAL ALLERGIES. Issue 1 (1st January 2007) - Helm, M. E.; Jones, S. M.; Kloepfer, K. M.
Abstract : Purpose: Due to increasing Medicaid costs in prescription medicine, the State of Arkansas implemented an evidence based prescription drug program in 2004. Preferred drugs for the treatment of several common conditions were identified. One group of medicines addressed was the less sedating antihistamines. Loratadine was chosen based on the lack differences in total symptom scores when the agents were compared with each other in regular use and due to the significantly higher costs of the other agents. Methods: Using administrative claims data, all antihistamine-treated patients in Arkansas Medicaid and SCHIP programs were identified. Data on antihistamine prescriptions were gathered over 18 months, including 3 months prior to implementation of a preferred nonsedating antihistamine program. Results: Dramatic changes were seen in the prescribing patterns of physicians. Prior to the implementation of the preferred drug in March 2005, 2.5% of prescriptions for less sedating antihistamines were for loratadine. After it became the preferred drug, up to 87% of prescriptions were for loratadine. A decrease in Medicaid net cost was also seen. In the 15 months since implementation, there have been at least $3.1 million in net costs avoided. Patients with prior authorization (PA) were allowed to continue their nonpreferred prescription as long as they met filling criteria of four refills within the previous 6 months. Of those, 1, 860 patients received PA for nonpreferred less sedating antihistamines, and 1, 542 filled the prescription. Only 47% of these patients filled their prescriptions four or more times within a 6-month period. Conclusion: Some patients granted PA for a nonpreferred antihistamine never filled their prescription. Around 50% of patients receiving PA filled their prescription three or fewer times in 6 months. Patients are occasionally using prescription antihistamines for symptomatic relief. Medicaid has saved over 3.1 million by using loratadine as their preferred drug for the treatment of seasonal allergies. Thus far, there has been no detectable negative impact on patient care.